Iatrogenic Acute Ascending Aortic Dissection with Intramural Hematoma during Coronary Artery Stenting: A Case Report - El-Haress, Mohamad; Daadaa, Hicham; Shahjouei, Shima; El-Bitar, Firas; Bahmad, Hisham (Frontiers in Surgery, 2017)
Background: Iatrogenic acute ascending aortic dissection during percutaneous coronary intervention (PCI) is an exceptionally rare and life-threatening sequel that requires early and accurate diagnosis along with rapid management. No guidelines have yet been established to direct decisions on the different treatment options that can be employed in the setting of acute aortic dissections caused by PCI. However, similar cases have been treated either by intracoronary stenting and conservative management as in localized aortocoronary dissections, or by surgical intervention in cases of extensive aortic dissections. Case summary: Hereby, we present a rare case of a female patient who developed “full-blown” acute ascending aortic dissection (Stanford type A - DeBakey type II dissection) with intramural hematoma during an elective percutaneous transluminal coronary angioplasty (PTCA) of the right coronary artery (RCA) and left circumflex artery (LCA). Accordingly, emergent surgical repair of the dissected aorta was performed including grafting of supracoronary ascending aortic tube, along with coronary artery bypass graft (CABG) placement and septal myomectomy for severely hypertrophied cardiac septum. The patient recovered successfully without any documented postoperative complications. Conclusion: It is pivotal to avoid aggressive use of instrumentation during PTCA in order to prevent the potential development of catheter-induced aortic dissection.